Proses Agenda Setting Kebijakan Hutan Adat Di Kabupaten Mentawai - Sulthani, Aisyah Fadilla (Jurnal Administrasi dan Kebijakan Publik, 2019)
This research is motivated by the decision of the Constitutional Court Number 35 / PPU-X / 2012 which states that Customary Forest is no longer a forest in the territory of the country but a forest that is part of the rights of the Customary Law Community. n Mentawai Islands Regency, almost 90% of the area is forested areas, 26,000 hectares will be converted into Customary Forests. In its determination, the community was assisted by the Foundation of Citra Mandiri Mentawai or Yayasan Citra Mandiri Mentawai (YCMM) and the Alliance of Mentawai Indigenous Community or Aliansi Masyarakat Adat Mentawai (AMAN) in realizing the rights of indigenous peoples. This study aims to describe how the process of setting agenda of customary forest policy in Mentawai Islands Regency. The method used in this study is qualitative descriptive. Data collection techniques in this study are interviews, and literature studies using various literature such as books, scientific works, news, and other reading sources relating to research. The results of the study showed that the problem was felt by the Mentawai community since they could not cultivate the forest themselves. After the Constitutional Court's decision No. 35 / PPU-X / 2012, the community assisted by NGOs and the local government drafted a regional regulation related to the recognition of indigenous community, which is one of the requirements to establish customary forests. The Regional Representative Council or DPRD is the only hope of the indigenous community to gain freedom that had not been obtained for several years before the Constitutional Court's decision No. 35 / PPU-X / 2012 was issued. But in the process, the DPRD has not yet stipulated a regional regulation on the recognition of customary law communities since it was submitted in 2015 until now in 2017. It is unfortunate that the DPRD of Mentawai Islands Regency has been slow to respond to demands from NGOs and the community so that discussion of the Draft Law on the Protection of Indigenous Community pendingtakeholdernya